Chemical and cultural management strategies for glyphosate-resistant sourgrass in central Brazil - Correia, Núbia Maria (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate different chemical treatments, associating herbicide combinations with the maintenance of forage species in the off-season, for the management of glyphosate-resistant sourgrass (Digitaria insularis) in a soybean crop. The experimental design was a randomized complete block in a 4×5 split-plot arrangement, with four replicates. The treatments consisted of: four combinations of the clethodim, glyphosate, haloxyfop-p-methyl, glufosinate ammonium, and s-metolachlor herbicides in the plots; green covers with the Massai, BRS Tamani, and BRS Zuri cultivars of Panicum maximum and with Urochloa ruziziensis, as well as fallow, in the subplots; and a control with the isolated application of glyphosate at the desiccation and post-emergence of the soybean crop infested with sourgrass and weeded. The herbicides tested before sowing and at post-emergence of soybean promoted a control above 90% of adult sourgrass plants until grain harvest. After harvest, there was a new emergence of sourgrass, mainly in the plots without green cover in the off-season. Overseeding soybean with forage species allowed of the establishment of these plants, which consequently interfered in sourgrass emergence and growth. The chemical treatments with herbicide combinations associated with the maintenance of forage species in the off-season are effective for the control of adult glyphosate-resistant sourgrass plants.